SISTEM INFORMASI PADA PEMADAM KEBAKARAN UNTUK MENUNJANG KUALITAS PELAYANAN DI KANTOR UPTD PEMADAM KEBAKARAN KABUPATEN POLEWALI MANDAR - Sri Yuyun (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2019)
In general, this study aims to analyze and describe the responsiveness of information systems and fire fighting services to the PolytaliMandar District Fire Extinguisher UPTD. This research use desciptive qualitative approach. The data collection methods used are interviews with informants and observations made about approximately 1 month. The results of this study indicate that in general the responsiveness of information systems and services of PolewaliMandar District fire department is less responsive. According to the results of the research based on indicators of responsiveness, there are some shortcomings found, among others, the lack of firefighters in serving public demand because they are often constrained by road access, facilities and infrastructure, the PolewaliMandar district fire brigade is old and not feasible to operate optimally.